Implementation of Integrated Management to Achieve Economic Growth of Wanagriya Tourism Village Ciseeng Bogor: Utilization of Financial Technology, E-Commerce, and HR Development - Ludvy, Achmad; Amelia, Rizka Wahyuni (Journal of Business Management and Economic Development, 2025)
This research aims to find out how to utilize Financial Technology, E-commerce, and HR development in an integrated manner to achieve economic growth in the Wana Griya Ciseeng Bogor Tourism Village. This research is an associative causal analysis that analyzes the concept of the relationship between the independent variable and the dependent variable in describing an integrated analysis concept, so this type of research is included in the combined/mixed qualitative and quantitative research method with analysis techniques using the analytical hierarchy process (AHP) concept using applications. Alpha-Sigma Calculator AHP. This research shows that in the integrated management concept, 3 main variables contribute to the development of the Wana Griya Tourism Village, Ciseeng Bogor. Financial Technology contributes 22.67%, E-commerce contributes 29.29%, and HR Development contributes 48.03% in the Integrated Management concept.